Reader (book) – Muslim perspective of world religions: selected themes - Kamaruzaman, Kamar Oniah (s.n, 2012)
This is a study of the fundamental theologies and doctrines of world religions and viewing these from the Islamic perspective. Although there are similarities in the theologies and doctrines of the other religions, but these however are not identical to the Islamic theology and doctrines and therefore cannot be regarded as Islamic. The very premise of each theology is different and therefore also the theological doctrines. The differences are subtle and this study extracts these subtle differences and analyzes them from the Islamic perspective so that Muslims will not regard these teachings as parallel to Islamic teachings and therefore consistent with the Islamic ‘aqīdah (عقيدة); they are not. Each religion defines and interprets the theological and doctrinal items in its own ways and therefore has its own worldview-views and value systems. Thus, each religion has its own unique characteristics, and has its own identity and as such, each religion is a wholesome entity on its own.